THE PSYCHOLOGICAL IMPACT OF PUNISHMENT ON ANDREW NEIMAN IN THE WHIPLASH MOVIE: OPERANT CONDITIONING APPROACH - Nur Kholilia, Alfi; Fitri Wulandari, Diyah (Universitas Duta Bangsa Surakarta, 2025)
A person's behavior can be studied using the Operant Conditioning method with one of its main concepts, namely punishment. Giving punishment to individuals will cause a significant impact. This research examines the impact of punishment on Andrew Neiman's character in the Whiplash movie. The purpose of this research is to find out the concept of punishment and its impact contained in the Whiplash movie based on Andrew's experience. The theory used in this research is the theory of Operant Conditioning developed by B.F. Skinner. This research uses data in the form of dialogue and narrative sentences from the Whiplash movie script which are then analyzed using qualitative descriptive methods. The results of the analysis show that the impact of the punishment received by Andrew is the emergence of negative feelings, the emergence of anxiety and depression and the widespread impact. Therefore, it can be concluded that the application of punishment can affect individual behavior.